Flavonoids - Natural Therapeutic Agents For Polycystic Kidney Disease - G.SHOBA; SHYAMALA HARI; G.PRABHAVATHI; SUGEETHA STELLA (International Journal of Pharma and Bio Sciences, 2010)
In the battle for a disease free world, focus is laid more on synthetic compounds as drugs without even bothering about the harmful side effects they produce. This study is a novel approach emphasizing the significance of natural products as a prime solution to unanswered questions like the treatment of the ‘Silent Killer’-“Polycystic Kidney Disease” (PKD). Flavonoids are one of the biologically active chemical constituents of plants. These natural products are readily available to man in the form of vegetables and fruits. The emergence of Bioinformatics has provided a platform to explore diseases at the molecular level using Computational techniques. Insilico methods are mainly harnessed to reduce the time, cost and risk associated with Drug Discovery. The key protein namely Cystic Fibrosis Transmembrane conductance Regulator which upon mutation plays major roles in cyst formation, fluid accumulation and hypertension in PKD is selected as drug target. The 3D structure is mutated and subjected to Molecular Docking with flavonoids from vegetable sources. Docking scores and Insilico Toxicity test result indicates the application of Flavonoids as Potential and Natural Therapeutic agents to combat PKD.